2021
DOI: 10.3389/fpsyt.2021.725197
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Social Capital and Depressive Symptoms Among Type 2 Diabetes Mellitus Patients in Northwest China: A Mediating Role of Sleep Quality

Abstract: Objective: There are few studies about the relationship between social capital (SC) and depression among type 2 diabetes mellitus (T2DM) patients, and the mechanism explaining how SC leads to decreased depression is unclear. The current study aims to explore the relationship between SC and depressive symptoms among the T2DM patients in northwest China, with a particular focus on the mediating role of sleep quality.Methods: A cross-sectional study of 1,761 T2DM patients from Ningxia Province was conducted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…These prevalence rates were higher than those reported in the general population [ 39 ]. In our study, the prevalence of depression was higher than Wang ’ s study [ 40 ]. However, another study found that the prevalence of depression and anxiety in patients with diabetes was higher than that in our study [ 41 ].…”
Section: Discussioncontrasting
confidence: 78%
“…These prevalence rates were higher than those reported in the general population [ 39 ]. In our study, the prevalence of depression was higher than Wang ’ s study [ 40 ]. However, another study found that the prevalence of depression and anxiety in patients with diabetes was higher than that in our study [ 41 ].…”
Section: Discussioncontrasting
confidence: 78%
“…A similar sampling procedure was described previously. 17 The total sample size was evaluated by the formula: n = Z 2 α/2 (1 - P)/ε 2 P. According to a previous study, the prevalence of quality of life in Chinese diabetes patients was 55%. 18 Hence, we set P = as 0.55 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited using PPS sampling. A related sampling procedure has been described formerly ( 21 ). The total sample size was evaluated by the formula: n = (1 - P)/ϵ2 P. According to a previous study, the prevalence of dyslipidemia in Chinese diabetes patients was 54.3% ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep duration was identified by two questions, “how early do you usually go to sleep at night and how early do you usually wake up” ( 26 ). Sleep quality was determined by poor/moderate/good responses to the question “how do you rate your sleep quality” ( 21 ).…”
Section: Methodsmentioning
confidence: 99%